Survey onidentification and classification of waste for efficient disposal and recycling - Prasanna M, Adhithya; Vikash Kaushal, S; Mahalakshmi, P (International Journal of Engineering and Technology, 2018)
Waste management is a pervasive problem in today’s world and is rising continuously with rise in urbanization. For ecologically sustainable development, waste management is a vital requirement in many countries. It is very essential to sort the waste at base level so that there can be proper disposal of waste at the dumping sites. Sorting of waste requires more manpower and consumes more time too. Waste can be sorted and managed in numerous types of techniques. Analysing and classifying the garbage using image processing can be a very productive way to process waste materials. These papers talk about the traditional methods in which waste disposals are taking place. These also talk about the drawbacks faced by the already existing systems and ways to overcome it.